Material- and Site-Specific Partition Coefficients for Beneficial Use Assessments - Blaisi, Nawaf, I; Clavier, Kyle A.; Roessler, Justin G.; Chung, Jaeshik; Townsend, Timothy G.; Al-Abed, Souhail R.; Bonzongo, Jean-Claude J. (American Chemical Society, 2019)
Partition coefficient (K-d) values available in the literature are often used in fate and transport modeling conducted as part of beneficial use risk assessments for industrial byproducts. Because element partitioning depends on soil properties as well as characteristics of the byproduct leachate, site-specific K-d values may lead to more accurate risk assessment. In this study, contamination risk to groundwater of beneficially reused byproducts was assessed using batch leaching tests on waste to energy bottom ash and coal combustion fly ash. Leachates were equilibrated with eight different soils to obtain the waste-soil-specific K-d,K-exp values for the metals of interest. The K-d,K-exp values were used as inputs in the Industrial Waste Management Evaluation Model to demonstrate the degree to which K-d estimates affect risk assessment outcomes. Measured K-d,K-exp values for the most part fell within the large range of K-d values reported in the literature, but IWEM results using default K-d values for some types of soils resulted in overestimated risk compared to those derived from K-d,K-exp values. Modeled concentration at the receptor location was much lower for some elements for those soils with high concentrations of iron and aluminum.
Keywords: REACTIVE TRANSPORT; SOLID-WASTE; METALS; DISPOSAL; SORPTION; IMPACT; MECHANISMS; FRAMEWORK; SOILS; ROADS